EDUKASI IBU HAMIL DAN BALITA DALAM UPAYA PENCEGAHAN STUNTING DI WILAYAH KERJA PUSKSMAS PAUH KOTA PADANG - Azrimaidaliza Azrimaidaliza; Yasirly Khairany; Rahmi Putri (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Stunting is a nutritional problem caused by lack of nutritional intake for a long time in the first 1000 days of life (HPK), which is a critical period, resulting in growth disorders in children, namely the child's height is lower or shorter (short) than the legal age. Stunting in West Sumatra increased by 5.1%, from 25.5% in 2016 to 30.6% in 2017. Pauh Health Center is the health center with the highest stunting incidence in Padang City, 31%. The activity aims to increase the knowledge and healthy behavior of pregnant women and mothers under five to prevent stunting. The stunting-themed educational activity was carried out on five cadre representatives from each kelurahan and 21 respondents consisting of 10 pregnant women and 11 mothers with toddlers. This activity is carried out through social media Whatsapp. Through this social media, devotees create groups and deliver materials using leaflets that have been previously designed as a health promotion tool. The distributed leaflet was entitled Prevent Stunting with Diet, Clean and Healthy Lifestyle During the First 1000 Days of Life. The educational activities went well and received a good response and enthusiasm from the respondents. This is shown by respondents' enthusiasm to ask questions and share information obtained through their social media accounts. The education provided was also well conveyed as indicated by the increase in respondents' knowledge regarding stunting by comparing the pre-test and post-test results. For this reason, educational activities using social media need to be continuously implemented to increase public knowledge, especially the nutritionally vulnerable groups, namely pregnant women and toddlers.